Electro-chemical mechanical polishing of copper and chemical mechanical polishing of glass - Venkatesh, Vasisht C.; Sudin, Izman; Mahadevan, S. C. (Elsevier B.V., 2004)
In IC and optical manufacturing some of the materials that are polished after grinding are Si, Ge, Pyrex and BK 7 glass. In the case of Al, Cu and W, they are deposited and are CMP polished. The polishing process used on IC wafers is chemical mechanical polishing (CMP) that has in built facilities for planarizing as well. There are two major applications in ultralarge scale integrated circuits (ULSI) manufacturing. One application is to smooth surface topography of interlevel dielectric (ILD), e.g. doped oxide or silicon oxide and another application is to remove excess Cu material to produce inlaid metal structures or isolation trenches. Cu CMP is employed for Cu metallization on oxide layers, which are patterned and etched to form vias, and trenches that are subsequently electroplated to fill with copper. Recent publications indicate evidence of copper undergoing electro-chemical mechanical interactions during polishing